FOMITE FACTORS AND SILENT SPREAD: A VSEIQCR STUDY OF VIRAL DISEASES - Soni, M.; Sharma, R. K.; Sharma, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2024)
This study investigates the impact of both detected and undetected viral cases, alongside environmental pathogens, on infection transmission dynamics. A VSEIQCR model is formulated and refined to analyze the study and to assess the basic reproduction number using the next-generation matrix method. The findings reveal a rapid escalation in viral cases, correlating with the rise in undetected cases. The study suggests that identifying and isolating individuals exposed to or infected by the virus, whether detected or undetected, is deemed imperative for curtailing disease transmission. Additionally, The study emphasizes the role of fomites in infection spread. It stands out for its innovative approach, examining the interconnections among vaccination, quarantine, and contamination strategies within a cohesive research framework, thereby setting a precedent in the field.